Peran Genetika pada Sifat Mengeram sebagai Dasar Seleksi pada Ayam Lokal: The role of genetics in brooding traits as a basis for selection in local chickens - Bilyaro, Woki; Rahman Azis, Arif; Muhammad dani; Rafian, Teguh; Nova Widyasari, Dhini; Ramadhanti, Nurazizah; Amrullah Chaniago, Rizky; Marisa, Anggun; Maharani Dwipassa, Virna (BPFP Universitas Bengkulu, 2025)
Broodiness is a natural reproductive behavior that plays a vital role in the success of hatching and maternal care in indigenous chickens. This behavior is governed by a complex interaction between endocrine and genetic factors, with the prolactin (PRL) gene serving as a key regulator. The prolactin hormone encoded by the PRL gene stimulates broody behavior, temporarily suppresses egg production, and enhances the maternal instinct to remain on the nest. Genetic variation in the PRL gene polymorphism is associated with the differences in the intensity and frequency of brooding behavior between chicken breeds and local populations. Specific alleles of the PRL gene are associated with increased broodiness, while others are linked to reduced expression and weakened maternal behavior. Studies on Indonesian local chickens demonstrate a significant upregulation of PRL expression during the brooding phase, confirming its central role in the regulation of reproductive behavior. These findings suggest that the PRL gene holds strong potential as a molecular marker in genetic selection programs. Through marker-assisted selection, breeders can maintain strong broody traits for natural hatching or suppress them to enhance egg productivity. Therefore, a deeper understanding of the structure, function, and genetic variability of the PRL gene provides a crucial foundation for developing adaptive, efficient, and sustainable breeding programs for indigenous chickens.